Notes to Philosophy 167: Class 12 -- Newton's Early Unpublished Work in Mechanics -- Part 5 - Part 6. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Newton's Work in Optics: 1665-1680 -- Newton's Early Laws of Motion (vs. Descartes, Huygens): Newton's Conceptualization of the Problem.; Generally corresponds to the video segment: Class 12, Part 5 - 6.